Modification of Structure and Strength Properties of Permanent Joints Under Laser Beam Welding with Application of Nanopowder Modifiers; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Cherepanov A. N.; Orishich A. M.; Malikov A. G.; Ovcharenko V. E. Vladimir Efimovich (2016, 2016)
Title screen